Correction: Association of dietary sodium intake with impaired fasting glucose in adult cancer survivors: A population-based cross-sectional study. - Kyuwoong Kim; Haemee Kim; Tae Jun; Young-Hak Kim (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0286346.].